Sensory discrimination tests and measurements : - Bi, Jian (Blackwell Pub., 2006)
Sensory discriminative analysis forms a fundamental type of methodology and is used widely in sensory and consumer research. Sensory Discrimination Tests and Measurements: Statistical Principles, Procedures and Tables provides a comprehensive discussion of sensory discriminative analysis from a statistical perspective. A wide variety of test and measurement methods, which were developed during the past decades and scattered in various statistical and non-statistical journals, are included in the book. The book gives a unified picture of the state of the subject and reflects some features of advanced sensory discriminative analysis. Designed to be both a reference manual and a research monograph, practitioners will discover various useful test and measurement procedures. More statistically-oriented readers will find the statistical considerations behind the procedures. Sensory Discrimination Tests and Measurements will be of interest to everyone concerned with testing and measuring sensory difference and consumer preference.